(untitled) (Fiep Bulletin - online, 2014)
The massage, as a manual resource, has been adopted by a growing number of professionals looking forward for wellness, stress reduction and pain relief. The aestheticician, with their ability to Epicrânia Massage, can help reducing muscle tension in the region of the face and head. This study investigated a group of 20 individuals of both sexes, carriers of temporomandibular dysfunction, aged 19 to 39 years. Underwent to 03 massage sessions (one per week and consecutive), each lasting 30 minutes. The screening was done with the DMF Anamnesic Index (Fonseca et al., 1994) and also clinical examination based on the Index of Temporomandibular Fricton and Shiffman (2002) was applied to check presence of muscle strain and cracking in the region of ATM. Before and after every massage sessions was conducted an assessment of the degree of opening, sliding sideways left and right, and protrusion of the mouth, with the measuring precision digital device caliper DIGIMESS. The results were presented in a graph and explanatory percentage. Thus, through this work we raise the benefits of massage Epicrânia technique in people who had muscle strains in temporomandibular joint (TMJ) caused by stress.